DAMPAK KEBIJAKAN PEMEKARAN WILAYAH KABUPATEN CIAMIS TERHADAP PENDAPATAN ASLI DAERAH (PAD). - Fitriyani Yuliawati (Jurnal Ilmu Politik dan Pemerintahan, 2021)
Ciamis Regency region regulation extended policy, is according to government regulation Number 27 year 2002. this regulation is  about  Banjar City Establishment In West Java Province. As the implementation of extended region Ciamis Regency, there is some questions about the condition of region income (PAD) at Ciamis Regency. The result of this research that obtained, the condition of region income of Ciamis Regency had been increase above 61,46 %, this revenue was increase from other region legally income for about 293 % and then this income following by region retribution for about 43,13 %, region tax for about 36,85 %, and local company profit 3,25 %. The increasing of region income Ciamis Regency was happened because Ciamis Regency made a great effort to increasing the revenue of Ciamis Regency after the implementation of extended region policy.in the procedure of increasing this region income the Ciamis Regency taking a few important steps which is : increase taxes tariff and adding the tax object, and then raising the retribution object, to made a good management fiscal from local company, and use the balancing of financial power between Central Government and Local Government as good as they can in the other legal region income.